Association Between Vitamin D Receptor Gene Polymorphisms, Inflammatory Cytokines (IL-1, IL-6, and IL-10), and Fracture Healing in Sports-Related Injuries: Inflammatory Cytokines (IL-1, IL-6, and IL-10 ) and Fracture Healing - Wang, Dan (Journal of Medical Biochemistry, 2025)
Background: In this study, we analyzed the correlation between polymorphisms in the Vitamin D receptors (VDR) gene at the Apa I and FoK I loci and sports-related fractures (SRF). We also examined the inflammatory cytokines IL-1, IL-6, and IL-10 to explore their potential role in fracture healing.Methods: A retrospective analysis was conducted on 110 patients with SRF admitted to our hospital from February 2023 to October 2023. Among these, 41 patients with poor fracture healing (research group) and 69 patients with good fracture healing (control group) were included. Serum levels of Vitamin D (VD), bone mineral density (BMD), and inflammatory cytokines (IL-1, IL-6, and IL-10) were measured to assess their relationship with fracture healing. Additionally, polymorphisms in the VDR gene at the Apa I and FoK I loci were analyzed for differences between the two groups.Results: The VD levels in the research group were significantly lower than in the control group (P